여성의 일-가정양립을 위한 육아문화와 기업의 사회적 공헌 - 서동희(Dong-Hee Seo) (한국콘텐츠학회 논문지, 8(2), 2008)
Considering the existing corporate culture, it's hard to compatible with work for the women and family and it brings a loss of human resources to government and corporate. But if the corporate realized the social responsibility for the childcare as one of the family-friendly culture, and had an aggressive will, it will be possible to break the way of traditional childcare, raise the competitiveness by expanding the work childcare facilities and laid a foundation for the social contribution. Thus, this study expressed the division of labor by gender culture should be changed to family-based women-friendly culture in the home and the corporate. And also this paper provides that, in the view of the corporate has to fully realize the social responsibility, the government properly supports the corporate which has family-friendly culture and through it, with pursuit of profit the corporate can ensure the social justice from social contribution. 기존의 기업문화를 고려하면, 여성들이 일과 가정의 양립이 어려워 국가나 기업의 측면에서 인력손실을 초래하였다. 그러나 기업이 조직내 가족친화적 문화의 하나로 육아에 대한 사회적 책임을 올바르게 인식하고 적극적인 의지를 갖게 된다면 전통적 육아의 방식을 탈피하고, 노동시장 내의 직장보육시설 확대를 통한 경쟁력제고와 더불어 사회적 기여를 할 수 있는 토대가 마련될 수 있을 것이다. 따라서 본 연구는 성별분업의 문화가 가정 내에서 뿐만 아니라 기업에서도 가족중심의 가족친화적 문화로 변화를 이루어야 함을 피력하고, 직장보육시설의 확대를 위해 기업이 사회적 책임을 통감해야 한다고 보는 관점에서 정부는 가족친화적 조직문화를 지닌 기업을 적절하게 지원하고 이를 통해 기업은 이윤추구와 더불어 사회적 공헌을 하여 사회적 정당성을 확보할 수 있음을 밝힌다.